Life after training: professional experiences of recently qualified clinical and counselling psychologists in South Africa - Haine, Phillipa (Rhodes University, Faculty of Humanities, Department of Psychology, 2020)
Professional psychology in South Africa has experienced numerous transformations since its tainted historical affiliation with the apartheid regime. However, despite the profession's attempts to respond to the burgeoning mental health needs of the country, psychologists in South Africa continue to be confronted by a number of challenges within the professional field. International research suggests that early career psychologists, in particular, experience further challenges in adjusting to new professional careers. Considering the dearth of research on this topic within local literature, the aim of this study was to gain an in-depth understanding of the lived professional experiences of recently qualified clinical and counselling psychologists in South Africa, following training. An interpretive phenomenological method was employed to investigate the fundamental early career professional experiences of participants, as well as the meanings participants attributed to these experiences. Four participants were recruited using purposive sampling. Data was collected through the use of semi-structured, one-on-one, Skype interviews, and the interview data were analysed using interpretative phenomenological analysis. The study revealed four super-ordinate themes, including: (i) Training as a 'rite of passage'; (ii) Expectations for a professional future; (iii) Professional psychology: Entering the work space; and (iv) Future directions. The findings suggest that clinical and counselling psychologists' experiences as recently qualified professionals in South Africa are both positive and negative, with the overall experience being positive. Emerging themes suggest that early career psychologists are faced by a number of personal and professional challenges on entering the work place. Furthermore, findings suggest that the early career experiences of recently qualified clinical and counselling psychologists in South Africa might not necessarily be due to personal choice, but rather due to greater systemic factors, such as limited available posts, maladministration, the devalued status of mental healthcare in comparison to other healthcare concerns in the country, an unresponsive marketplace and limited efforts by government to accommodate psychologists in different contexts
Keywords: Clinical psychologists - -- South Africa; Counseling psychologists - -- South Africa; Psychologists -- Job stress -- South Africa; Psychologists -- Employment -- South Africa; Career development -- South Africa; Psychologists -- Training of -- South Africa; Life change events; Qualitative research